Career Interest and Work Values of Online Filipino Psychology Graduates: Basis for Retention Program - Cardiño, Henmar; Sario, Erwin; Sergio, Rommel (Social Sciences and Development Review, 2025)
The main objective of the study is to evaluate the significant association between career interests and workplace values among Filipino online psychology graduates in 2022 and to provide retention strategies for diverse organizations. The study’s goal was to identify the gap between the participants’ career interests and their work values and offer possible retention programs to bridge the gap. The researcher employed a quantitative correlational research design and utilized two research instruments, the RIASEC Test by John L. Holland and the Work Values Inventory by Ronald E. Super, to measure career interest and work values, respectively. In August 2022, a total of 80 Filipino graduates of the psychology program gathered, representing almost 18 colleges and universities and six regions in the Philippines. Studies show that (1) Conventional, Social, and Investigative are the main characteristics of Filipino 2022 Psychology graduates; (2) Work Values such as Achievement, Supervisory Relationships, Surroundings, Altruism, Economic Return, Way of Life, Creativity, and Security are rated as very important by the target respondents. While, Prestige, Associates, Independence, Variety, Aesthetic, Intellectual Stimulation, and Management are rated as important; (3) Filipino Psychology graduates in 2022, there is a marginally favorable association between career interest and work values.; and (4) Competitive benefits package and generous salary, recognition and rewarding employees, management involvement, corporate social responsibility, mental health policies and programs, and work-life alignment are the proposed retention programs.
Keywords: career interest; work values; Psychology graduates; online class; retention program